A phase I study of daily afatinib, an irreversible ErbB family blocker, in combination with weekly paclitaxel in patients with advanced solid tumours. Issue 16 (November 2015) - Suder, A.; Ang, J.E.; Kyle, F.; Harris, D.; Rudman, S.; Kristeleit, R.; Solca, F.; Uttenreuther-Fischer, M.; Pemberton, K.; Pelling, K.; Schnell, D.; de Bono, J.; et al.
Abstract Background This phase I study evaluated afatinib, an irreversible ErbB family blocker, plus paclitaxel in patients with advanced solid tumours likely to express human epidermal growth factor receptor (HER1/EGFR) or HER2. Methods Oral afatinib was combined with intravenous paclitaxel (80 mg/m2; days 1, 8 and 15 every four weeks) starting at 20 mg once daily and escalated to 40 and 50 mg in successive cohorts of ⩾3 patients. The primary objective was to determine the maximum tolerated dose (MTD) of afatinib combined with paclitaxel. Secondary objectives included safety, pharmacokinetics and antitumour activity. Results Sixteen patients were treated. Dose-limiting toxicities with afatinib 50 mg were fatigue and mucositis. The MTD was determined as afatinib 40 mg with paclitaxel 80 mg/m2, which proved tolerable with repeated dosing. Frequent adverse events (AEs) included diarrhoea (94%), fatigue (81%), rash/acne (81%), decreased appetite (69%) and inflammation of mucosal membranes (69%); no grade 4 treatment-related AEs were observed. Five (31%) confirmed partial responses were observed in patients with non-small cell lung cancer (n = 3), oesophageal cancer and cholangiocarcinoma; eight (50%) patients remained on study for ⩾6 months. Pharmacokinetic parameters of afatinib and paclitaxel were similar for single administration or in combination. Conclusions The MTD and recommended phase II dose of once-daily afatinib combined with paclitaxel 80 mg/m2 (days 1, 8 and 15 every four weeks) was 40 mg. AEs at or below this dose were generally manageable with repeated dosing. No pharmacokinetic interactions were observed. This combination demonstrated promising antitumour activity. Trial registration ClinicalTrials.gov, NCT00809133.